The consumer-based brand equity inventory: Scale construct and validation - Bruno Schivinski; Dariusz Dabrowski (Gdańsk University of Technology, Faculty of Management and Economics, 2014)
The present study aims to meet the need for a refinement of the consumer-based brand equity scale and to address the limitations of the previous research on the subject. Based on previous measurements of brand equity, CBBE is conceptualized in this study as a four-dimensional model consisting of brand awareness, brand association, perceived quality, and brand loyalty. A sample of 1874 Polish consumers was used to test the proposed dimensions. To measure the construct, we used a combination of exploratory and confirmatory factor analyses employing structural equation modeling in 12 product categories and across 24 brands. Additionally, for the purpose of cross-validation, we tested the framework for the factorial invariance of instrument scores. The results of our research support the hypothesized four-factor CBBE model. Moreover, the subscales designed to measure the construct operate equivalently across different product categories, which allows the meaningful comparison of scores and a wider empirical application.
Keywords: M30; M31; Y1; 330; consumer-based brand equity; brand awareness; brand associations; perceived quality; brand loyalty